Pediatric germ cell tumors presenting beyond childhood?. (27th November 2014) - Oosterhuis, J. W.; Stoop, J.A.; Rijlaarsdam, M. A.; Biermann, K.; Smit, V.T.H.B.M.; Hersmus, R.; Looijenga, L. H. J.
Summary: Four cases are reported meeting the criteria of a pediatric (i.e., Type I) testicular germ cell tumor (TGCT), apart from the age of presentation, which is beyond childhood. The tumors encompass the full spectrum of histologies of pediatric TGCT: teratoma, yolk sac tumor, and various combinations of the two, and lack intratubular germ cell neoplasia/carcinoma in situ in the adjacent parenchyma. The neoplasms are (near)diploid, and lack gain of 12p, typical for seminomas and non‐seminomas of the testis of adolescents and adults (i.e., Type II). It is proposed that these neoplasms are therefore late appearing pediatric (Type I) TGCT. The present report broadens the concept of earlier reported benign teratomas of the post‐pubertal testis to the full spectrum of pediatric TGCT. The possible wide age range of pediatric TGCT, demonstrated in this study, lends credence to the concept that TGCT should according to their pathogenesis be classified into the previously proposed types. This classification is clinically relevant, because Type I mature teratomas are benign tumors, which are candidates for testis conserving surgery, as opposed to Type II mature teratomas, which have to be treated as Type II (malignant) non‐seminomas.